MORPHO-HISTOLOGICAL CHARACTERISTICS OF BRUISES WITH DIFFERENT AGE -qualitative study - Irena Kostadinova Petrova; Elida Mitevska; Lena Kakasheva-Mazhenkovska; Ljubica Tasheva; Natasa Stojkovska; Biljana Janeska (Macedonian Association of Anatomists, 2022)
Bruises are common skin lesions that occurastheforce hits the skin, but integrity of the skin is not impaired. Their significance isimportantinforensic expert reports in determining the time of death in many cases of domestic violence or child abuse. The aim of this study was to present the differences between bruises with different time of origin by evaluation of their morpho-histological characteristics.The study included 60 human skin samples divided into control and experimental groupsA, B, C, D.The experimental group A included bruised human skin samples with <1dayold bruises, experimental group B included bruised human skin samples with 1-3 days old bruises, experimental group C included bruised human skin samples with 3-7 days old bruises and experimental group D included bruised human skin sampleswith 7-14 days old bruises. Paraffin sections of the skin were stained withHematoxylin-eosin, Giemsa, Perl’s Prussian Blue, Masson-Goldner methods of staining and application ofanti-HO-1 antibody. All paraffin sections were evaluated by lightmicroscopy andphotodocumented.Our results have shown changes in color in bruises with different age due to infiltration with different immune cells and metabolism of extracellular hemoglobin. Granulocyte infiltration is seen shortly after the initiation of the bruise, whileafterfewdays of initiation, usually 1-3, there is macrophage infiltration in the field of bleeding. Presence of macrophages in the field of bleeding increases as bruises age. These histological characteristics appear in direction of healing the bruise, together with phagocytosis of the erythrocytes and removing the tissue debris.
Keywords: bruises; time of origin; morpho-histological characteristics; microscopic analysis.